2017
DOI: 10.1097/rlu.0000000000001379
|View full text |Cite
|
Sign up to set email alerts
|

Change in Salvage Radiotherapy Management Based on Guidance With FACBC (Fluciclovine) PET/CT in Postprostatectomy Recurrent Prostate Cancer

Abstract: Purpose We explored the influence of FACBC (fluciclovine) positron emission tomography-computed tomography (PET-CT) on the decision to offer radiotherapy and radiotherapy treatment field recommendations in post-prostatectomy patients with recurrent prostate cancer. Materials and Methods Following institutional review board approval and informed consent, 87 patients with detectable prostate specific antigen (PSA) were recruited into a prospective clinical trial. Following an initial provider-determined radiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 46 publications
2
47
0
Order By: Relevance
“…18F-fluciclovine (FCV) is a positron emission tomography (PET) radiopharmaceutical used for the detection of recurrent prostate cancer in adult men after primary curative treatment with the suspicion of recurrence based on elevated prostate-specific antigen (PSA) level [1]. The sensitivity of 18F-FCV PET for detecting recurrent disease increases with rising levels of PSA [2], the specificity for prostate bed in recurrent disease being 40-75%, as the residual prostate gland tissue is prone to uptake due to inflammation or prostatic hyper-trophy, the specificity for extraprostatic lesions was reported 97 and 100% [1,3,4]. FCV is accumulated by prostate cancer cells via specialised amino acids transporters, predominantly alanine-serine-cysteine transporter 2 (ASCT2) with contribution of l-amino acid transporter 1 (LAT-1) [1].…”
Section: Introductionmentioning
confidence: 99%
“…18F-fluciclovine (FCV) is a positron emission tomography (PET) radiopharmaceutical used for the detection of recurrent prostate cancer in adult men after primary curative treatment with the suspicion of recurrence based on elevated prostate-specific antigen (PSA) level [1]. The sensitivity of 18F-FCV PET for detecting recurrent disease increases with rising levels of PSA [2], the specificity for prostate bed in recurrent disease being 40-75%, as the residual prostate gland tissue is prone to uptake due to inflammation or prostatic hyper-trophy, the specificity for extraprostatic lesions was reported 97 and 100% [1,3,4]. FCV is accumulated by prostate cancer cells via specialised amino acids transporters, predominantly alanine-serine-cysteine transporter 2 (ASCT2) with contribution of l-amino acid transporter 1 (LAT-1) [1].…”
Section: Introductionmentioning
confidence: 99%
“…jnm.snmjournals.org Downloaded from planning mostly relies on conventional imaging, which may be unrevealing in the initial stages of prostate cancer recurrence. In a study involving 42 post prostatectomy patients randomized to undergo 18F-fluciclovine PET-CT after conventional radiotherapy planning, radiotherapy decisions were changed in 40.5% of patients after 18F-fluciclovine PET (24). However, the authors noted there was no statistically significant impact in this study on whether to actually offer radiotherapy, as only 2 of 42 patients had radiotherapy cancelled due to evidence of extrapelvic disease.…”
Section: Therapy Managementmentioning
confidence: 82%
“…For personal use only. jnm.snmjournals.org Downloaded from detection rates in the post-prostatectomy biochemical failure setting of 72.0%, 83.3%, and 100% at PSA levels < 1, 1-2, and ≥2 ng/ml respectively (24). A mixed post-prostatectomy and nonprostatectomy cohort demonstrated a 18F-fluciclovine detection rate of 37.5% at PSA < 1, 77.8% at PSA 1-2, and 91.7% at PSA > 2, and 83.3% at PSA > 5 ng/ml (25).…”
Section: Recurrent Diseasementioning
confidence: 99%
“…The model uses the sensitivity and specificity of each imaging modality to estimate the number of true positives, true negatives, false positives and false negatives to predict the health outcomes of the testing. Published clinical trial results were used to inform the test specification inputs for imaging of prostate cancer recurrent in the prostate bed and with extraprostatic involvement (Table 3) [8, [14][15][16][17]. Relevant studies were identified from Medline.…”
Section: Diagnostic Test Performance Specificationsmentioning
confidence: 99%